Evaluation of cowpea mini core accessions for resistance to flower bud thrips Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae) - Togola, A.; Boukar, O.; Chamarthi, S.; Belko, N.; Tamò, Manuele; Oigiangbe, N.; Ojo, J.; Ibikunle, M.; Fatokun, C. (Wiley, 2019)
The flower bud thrips, Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae), is an economically important pest of cowpea in sub‐Saharan Africa. Varietal resistance is the most preferred, environmentally friendly, cost‐effective and sustainable option for controlling this pest. The objective of this study was to identify sources of resistance to M. sjostedti among mini core accessions from the largest world cowpea germplasm collection maintained at the International Institute of Tropical Agriculture (IITA). The study was conducted during the 2015 and 2016 cropping seasons where 365 accessions were screened under field conditions. Each accession was rated visually for thrips damage score, flower abortion rate, number of pods per plant and number of thrips per flower. The resistance levels observed in genotypes TVu8631, TVu16368, TVu8671 and TVu7325 were similar to that of the resistant check “Sanzisabinli” (called Sanzi) during both seasons. In addition, 56 mini core genotypes showed moderate resistance to thrips damage. High heritability values were associated with thrips damage scores at 65 days after planting (0.60), percentage of effective peduncles (0.59), flower bud abortion rate (0.59), number of pods per plant (0.51) and number of peduncles with pods (0.5). The accessions identified with good levels of resistance to flower bud thrips will be used in cowpea breeding programs to develop improved resistant varieties.